DEVELOPMENT OF A MODULE ON EQUATIONS AND SQUARE FUNCTIONS TO IMPROVE THE MATHEMATICAL PROBLEM SOLVING CAPABILITY OF CLASS IX PRIVATE CHRISTIAN SMP BNKP TELUKDALAM - Sarumaha, Euphronius Randri Putra (Universitas Nias Raya, 2023)
This study aims to develop a module on quadratic equations and functions to improve students' skills in solving mathematical problems. The type of research used in this research is research and development (R&D), namely the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were students of class IX (nine) Christian Private Middle School BNKP Telukdalam Academic Year 2021/2022. In developing this module there are several stages, namely: (1) Analysis (Analysis), (2) Design (Design), (3) Development (Development), (4) Implementation (Implementation) and (5) Evaluation (Evaluation). After the module is in such a way, the module is ready to be validated by experts design, material experts and linguists. Based on the results of research on the development of mathematics learning modules from the three validation expert lecturers on mathematics learning modules classified as